2021
DOI: 10.3399/bjgp.2021.0054
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prescription of drugs used for insomnia: an open-cohort study in Australian general practice, 2011–2018

Abstract: Background: Despite an increase in the prevalence of sleep problems, few studies have investigated changes in the prescribing of drugs often used for managing insomnia. Aim: To explore changes in the pattern of benzodiazepine (BZD), z-drugs (zolpidem, zopiclone) and non-BZD prescriptions. Design and Setting: Open cohort study including 1,773,525 patients (55,903,294 consultations) regularly attending 404 Australian general practices from 2011-2018 (MedicineInsight). Method: Prescription rates per 1,000 consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 46 publications
5
26
1
1
Order By: Relevance
“…Also, we did not consider repeats for the investigated BZD prescriptions (approximately 10% of all BZD scripts provided in general practice between 2011 and 2018 had one or more repeats). 6 Our findings are consistent with results from other high-income countries, such as the US and Canada. 11,14 The odds of benzodiazapine use in the US between 1999 and 2014 increased for mediumterm (Odds Ratio [OR] = 1.45) and for long-term use (OR = 2.17).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Also, we did not consider repeats for the investigated BZD prescriptions (approximately 10% of all BZD scripts provided in general practice between 2011 and 2018 had one or more repeats). 6 Our findings are consistent with results from other high-income countries, such as the US and Canada. 11,14 The odds of benzodiazapine use in the US between 1999 and 2014 increased for mediumterm (Odds Ratio [OR] = 1.45) and for long-term use (OR = 2.17).…”
Section: Discussionsupporting
confidence: 91%
“…32 A previous study using MedicineInsight data also showed that despite a decrease in total BZD and related drugs, there has been an increased proportion of patients with a clinical history of insomnia or sleep problems receiving these medications. 6 These findings are consistent with evidence of a recent qualitative paper examining GPs perceptions on managing insomnia. The 2020 study highlighted the challenges faced by GPs when they treat patients with long-term medication dependence, especially given that support services and referral pathways can be difficult to access.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Simultaneously, most drugs mainly effect on anti-anxiety, sedation and hypnosis, and long-term use may produce adverse reactions and drug dependence. [ 5 ] In addition, it is easy to relapse or appear withdrawal symptoms after drug stopping. [ 6 ] Acupuncture is an important part of traditional Chinese medicine, and has been widely used in China and some western countries.…”
Section: Introductionmentioning
confidence: 99%